Philippine folk literature : the epics - Eugenio, Damiana L. (Diliman Quezon City, Philippines : University of the Philippines Press, 2018)
This volume of Philippine folk epics is the culminating volume of my Philippine folk litearture series. This series was originally planned to consist of seven volumes only, the epic being considered thean as being so dignified and awesome a form as to deserve nothing less than publication in full of each individual epin.
Preface to the second edition -- Preface -- Introduction -- The Life of Lam-ang -- Hudhud hi aliguyon -- The Kalinga ullalim -- Limalindaw -- The Ibalon -- The Epic of Lawba Donngon -- Kudaman -- The Maiden of the buhong sky -- Tuwaang attends a wedding -- Agyu: The Iliano epic of Mindanao -- Ulahingin -- Agyu: the capture of Nalandangan -- Matabagka searches for the deity of the wind -- Olaging: the battle of nalandangan -- Tulalang Slays the dragon -- Radia Indarapatra -- Darangan -- The Story of bantugan -- Maharadia lawana -- The Guman of dumalinao -- The Kingdom of Keboklagan -- The Tale of sandayo -- Tudbulul -- Bibliography -- About the author.
Includes bibliographical references.
Keywords: EPIC POETRY -- PHILIPPINES